2023
DOI: 10.1038/s41467-023-42292-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired trimesic acid anchored electrocatalysts with unique static and dynamic compatibility for enhanced water oxidation

Xiaojing Lin,
Zhaojie Wang,
Shoufu Cao
et al.

Abstract: Layered double hydroxides are promising candidates for the electrocatalytic oxygen evolution reaction. Unfortunately, their catalytic kinetics and long-term stabilities are far from satisfactory compared to those of rare metals. Here, we investigate the durability of nickel-iron layered double hydroxides and show that ablation of the lamellar structure due to metal dissolution is the cause of the decreased stability. Inspired by the amino acid residues in photosystem II, we report a strategy using trimesic aci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The smaller nanoplatelet surfaces of su-nfe-ldh(TA)@cp were much rougher and exhibited superhydrophilicity. These apparent changes suggest that the insertion layer formed by cyanuric acid increases the rate of electrolyte diffusion on the surface and between the layers [124]. In addition, the cavitation effect due to bubble rupture can severely damage the nanostructures, and the evolution of bubbles on the electrode surface affects the stability of the structure [125].…”
Section: Bioinspired Trimesic Acid Anchored Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller nanoplatelet surfaces of su-nfe-ldh(TA)@cp were much rougher and exhibited superhydrophilicity. These apparent changes suggest that the insertion layer formed by cyanuric acid increases the rate of electrolyte diffusion on the surface and between the layers [124]. In addition, the cavitation effect due to bubble rupture can severely damage the nanostructures, and the evolution of bubbles on the electrode surface affects the stability of the structure [125].…”
Section: Bioinspired Trimesic Acid Anchored Electrocatalystsmentioning
confidence: 99%
“…(d-f) In situ dete tion of precipitation behavior of O2 on NiFe LDH@cp, NiFe-LDH(TA)@cp, and SU-NiF LDH(TA)@cp at 10 mAcm −2 , respectively. Reproduced with permission from[124], © 2023 Natu Publishing Group.…”
mentioning
confidence: 99%
“…18−20 It has been demonstrated that the OER activity of metal oxides can be significantly enhanced by accelerating proton transfer, thereby facilitating the CPET process. 21,22 Expediting the deprotonation of oxo-intermediates is a promising direction that improves the OER kinetics of Rubased catalysts in acidic electrolytes. 23−25 However, in low pH environments, the deprotonation process of intermediates is influenced by the proton-rich conditions, leading to proton accumulation on the catalyst surface and the corrosion of active sites.…”
Section: ■ Introductionmentioning
confidence: 99%